The association between change of soluble tumor necrosis factor receptor R1 (sTNF-R1) measurements and cardiovascular and all-cause mortality—Results from the population-based (Cardiovascular Disease, Living and Ageing in Halle) CARLA study 2002–2016 - Hassan, Lamiaa; Medenwald, Daniel; Tiller, Daniel; Kluttig, Alexander; Ludwig-Kraus, Beatrice; Kraus, Frank Bernhard; Greiser, Karin H.; Mikolajczyk, Rafael (PloS one, 2020)
Single measurements of higher levels of soluble tumor necrosis factor receptor I (sTNF-R1) have been shown to be associated with increased risk of mortality. However, up to date, little is known about the underlying temporal dynamics of sTNF-R1 concentrations and their relation with mortality. We aimed to characterize the effect of changes in sTNFR-1 levels on all-cause and cardiovascular mortality, independent from other established risk factors for mortality, including other inflammatory markers. We used data of the population based cohort study CARLA and included 1408 subjects with sTNF-R1 measured at baseline (2002-2006) and first follow-up (2007-2010). Cox proportional hazard models were used to assess the association of baseline and follow-up sTNF-R1 measurements with all-cause and cardiovascular mortality during ~10 years since the first follow-up after adjusting for relevant confounders. Based on 211 deaths among 1408 subjects, per each doubling of the baseline sTNF-R1, the risk of all-cause mortality was increased by about 30% (Hazard ratio 1.28, 95% Confidence Interval 0.6-2.7), while per each doubling of the follow-up level of sTNF-R1 mortality was 3-fold (3.11, 1.5-6.5) higher in a model including both measurements and adjusting for confounders. The results were mainly related to the cardiovascular mortality (5.9, 2.1-16.8 per each doubling of follow up sTNF-R1 value). Solely the follow-up value, rather than its change from baseline, predicted future mortality. Thus, while sTNF-R1 levels are associated with mortality, particularly cardiovascular, over a long-time period in the general population, if they change, the earlier measurements play no or little role.